2015
DOI: 10.18805/lr.v38i5.5953
|View full text |Cite
|
Sign up to set email alerts
|

Effect of integrated nutrient management on growth, yield attributes and yield of field pea (<italic>Pisum sativum</italic> L) cv. Rachna

Abstract: A field experiment was conducted during the <italic>rabi</italic> season 2004-05 in a sandy clay loam soil to study the effect of inorganic fertilizers, organic manure and bio-fertilizers on growth, yield attributes and yield of field pea (<italic>Pisum Sativum</italic> L). It was observed that with increasing levels of inorganic fertilizers increased growth, yield and yield attributing characters. Farm yard manure @ 20 t ha<sup>−1</sup> and <italic>Rhizobium</itali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 0 publications
8
6
0
Order By: Relevance
“…The improvement in seed yield, haulm yield and harvest index were mainly on account of increase in the growth parameters and yield attributes of cowpea which resulted in higher production of photosynthates were utilized by the plant for development of sink under adequate supply of nutrients due to increasing in rate of inorganic fertilizer. These results are also in agreement with findings of Khandelwal et al, (2013), Sarawd et al, (2014), Khan et al, (2015), Qureshi et al, (2015), Satodiya et al, (2015), Sharma et al, (2015) and Joshi et al, (2018)…”
Section: Effect Of Inorganic Fertilizersupporting
confidence: 93%
See 2 more Smart Citations
“…The improvement in seed yield, haulm yield and harvest index were mainly on account of increase in the growth parameters and yield attributes of cowpea which resulted in higher production of photosynthates were utilized by the plant for development of sink under adequate supply of nutrients due to increasing in rate of inorganic fertilizer. These results are also in agreement with findings of Khandelwal et al, (2013), Sarawd et al, (2014), Khan et al, (2015), Qureshi et al, (2015), Satodiya et al, (2015), Sharma et al, (2015) and Joshi et al, (2018)…”
Section: Effect Of Inorganic Fertilizersupporting
confidence: 93%
“…Nitrogen enhances the development of strong cell walls and therefore stiffer branches which might be resulted into profuse branches of cowpea. These results are already in agreement with those reported by Sarkar et al, (1997), Sankar et al, (1999), Subbarayappa et al, (2009), and Qureshi et al, (2015).…”
Section: Effect Of Organic Manuressupporting
confidence: 93%
See 1 more Smart Citation
“…pod length (11.03 cm) was obtained in plots treated with Rhizobium@30g/kg of seeds and maize stubbles@4t/ha. It was concluded that increase in pod length might be due to the fact that Rhizobium inoculation resulted in an increase in root nodulation through better root development and more nutrient availability resulting in vigorous plant growth and dry matter production which result in better pod formation (Qureshi et al, 2015). Mulches retained a higher amount of soil water with efficient use of nutrients which might have enhanced plant growth.…”
Section: Yield Parametersmentioning
confidence: 99%
“…Another reason for the increase in yield can be related to the nitrogen fixation ability of nodules, which consequently resulted in increased yield in field pea Erman et al (2009). Qureshi et al (2015) reported that increase yield may be due to the fact that Rhizobium inoculation increased root nodulation through better root development and mere nutrient availability resulting in vigorous plant growth and dry matter production resulting in better flowering, fruiting and pod formation.…”
Section: Yield Parametersmentioning
confidence: 99%